Family physician system in Taiwan. Issue 2 (February 2020) - Jan, Chyi-Feng; Hwang, Shinn-Jang; Chang, Che-Jui; Huang, Cheng-Kuo; Yang, Hsiao-Yu; Chiu, Tai-Yuan
Abstract : Following economic development and increasing healthcare demand, Taiwan has not only built a universal healthcare coverage payment system in 1995, but has also developed an accountable family physician system, called the Family Practice Integrated Care Project (FPICP), to deal with the pressures of an ageing society, since 2003. The community healthcare group-based family physician system is not only an important milestone for the development of family medicine in Taiwan but may also even serve as a global example for future family doctor systems. In this review, we aim to review the development of family medicine in Taiwan, the implementation and achievement of the FPICP, as well as the future prospects of system-based healthcare system. We firmly believe that only when the family physician system is well developed and put into practice with person-centered, family as a care unit, and community-oriented holistic care, can the objective of "everyone has their own family doctor" and sustainable operation of National Health Insurance be achieved.